57=3+6(4x-7)

Simple and best practice solution for 57=3+6(4x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 57=3+6(4x-7) equation:


Simplifying
57 = 3 + 6(4x + -7)

Reorder the terms:
57 = 3 + 6(-7 + 4x)
57 = 3 + (-7 * 6 + 4x * 6)
57 = 3 + (-42 + 24x)

Combine like terms: 3 + -42 = -39
57 = -39 + 24x

Solving
57 = -39 + 24x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24x' to each side of the equation.
57 + -24x = -39 + 24x + -24x

Combine like terms: 24x + -24x = 0
57 + -24x = -39 + 0
57 + -24x = -39

Add '-57' to each side of the equation.
57 + -57 + -24x = -39 + -57

Combine like terms: 57 + -57 = 0
0 + -24x = -39 + -57
-24x = -39 + -57

Combine like terms: -39 + -57 = -96
-24x = -96

Divide each side by '-24'.
x = 4

Simplifying
x = 4

See similar equations:

| 7(4+7b)=-70 | | 18-3.8t=7.36-19t | | 2x^2-102x+14=0 | | 5n+4-8n=(-5) | | (u+8)(u-4)= | | -24=4(2-8r) | | -(1+6x)=14-x | | ln(8-6x)-2ln(x)=ln(2) | | 25-18+4(-2)= | | 3-4q=10q+100 | | W+1-5=2w | | 3x^15*x-36=0 | | 5x^2-27x+10=0 | | 7=x/2+5 | | 5y-3(y-2)+3= | | Q=xy-xy^2 | | 5+2x=3(2x+4)-5(x-2) | | 10-4(2w+1)=6w-4(6+w) | | -38=2k | | m+3n=7n | | 5(n+2)=3/5(5+10n) | | 7+3(3-2x)=7x+3(3x-2) | | 12=a-(-18) | | y^3+2y^2=0 | | -(7xy-10)+3(6xy+4)= | | -9/2(x+1)=3 | | 5x+3x^2-2x^3=0 | | 3=n-(-6) | | 0.5b+4=2+3d-0.5 | | 2(-8x+5)+5x=7(x+4) | | -6x+3(3x+12)=18 | | v+(-6)=-24 |

Equations solver categories